Toward Gene Therapy in Haemophilia A: Retrovirus-Mediated Transfer of a Factor VIII Gene into Murine Haematopoietic Progenitor Cells - Hoeben, R C; Einerhand, M P W; Briët, E; van Ormondt, H; Valerio, D; van der Eb, A J (Thrombosis and Haemostasis, 1992)
To study and evaluate the potential of the haematopoietic system as a target for gene therapy in haemophilia A, we have infected murine bone-marrow cells with a recombinant retrovirus encoding blood-coagulation factor VIII and the bacterial enzyme neomycin-phosphotransferase. After transplantation of the infected bone marrow into lethally irradiated mice, the presence of intact vector could be demonstrated in DNA isolated from individual haematopoietic progenitor-cell-derived spleen colonies. About 8% of the spleen colonies were shown to contain the intact vector. Selection for resistance to the neomycin analogue G418 prior to transplantation specifically killed the uninfected bone-marrow cells and, as a result, over 90% of the spleen colonies contained the factor VIII vector. However, expression of factor VIII in vivo, either at the RNA or at the protein level could not be demonstrated. From these data we conclude that: 1) retroviral vectors can be used to transfer factor-VIII cDNA into haematopoietic progenitor cells; 2) the vector sequences are expressed immediately after integration; and 3) transcription of the vector is repressed in the progenitor-cell-derived cells.